2017
DOI: 10.1111/trf.14085
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial screening of platelet components by National Health Service Blood and Transplant, an effective risk reduction measure

Abstract: The implementation of bacterial screening of PLT components with the NHSBT BacT/ALERT protocol was an effective risk reduction measure and increased the safety of the blood supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
159
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(173 citation statements)
references
References 37 publications
11
159
1
2
Order By: Relevance
“…Due to adhesion of bacterial cells to the inner surface of the platelet bags, a sampling error is very likely [48]. Similar findings are reported for S. aureus isolates, which escaped from the screening process despite late sampling [17]. To this end, S. aureus can form aggregates by direct interaction with platelets [49].…”
Section: Septic Reactions Due To False-negative Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…Due to adhesion of bacterial cells to the inner surface of the platelet bags, a sampling error is very likely [48]. Similar findings are reported for S. aureus isolates, which escaped from the screening process despite late sampling [17]. To this end, S. aureus can form aggregates by direct interaction with platelets [49].…”
Section: Septic Reactions Due To False-negative Resultssupporting
confidence: 61%
“…This benefit has been confirmed by several reports [11, 18, 39, 40]. For instance, a study from NHS Blood and Transplant showed that 66% of all confirmed positive results were only detected in anaerobic culture bottles, whereas 8% were positive in an aerobic and 26% in both bottle types [17]. It should, however, be noted that if both bottles are removed as soon as one of both is flagged as positive, it is unknown whether the second bottle would have led to a positive signal afterwards.…”
Section: Anaerobic Screening – Is It Worth the Effort?supporting
confidence: 66%
See 2 more Smart Citations
“…9 In the United States, samples for culture are taken at 24 to 30 hours after collection (vs 36-48 hours in the United Kingdom). In the United States, samples are typically 8 mL in aerobic culture and from the primary platelet bag, which then may be split into 1 to 3 platelet products, whereas the United Kingdom uses 8 mL in aerobic and anaerobic culture for each product.…”
Section: Alternatives Not Presented In Draft Guidancementioning
confidence: 99%